Does it pay to invest in dirty industries? New insights on the shunned-stock hypothesis - Michael Tobias Bauckloh; Victor Beyer; Christian Klein (University of Cologne, Centre for Financial Research (CFR), 2022)
This research examines whether stocks of firms operating in highly polluting industries ('dirty stocks') are treated like sin stocks. We assume that investors shun dirty stocks based on non-pecuniary preferences and employ screening approaches that lead to the exclusion of entire industries. Using emission data of the U.S. Toxics Release Inventory, we show that dirty stocks are held in lower proportions by institutional investors and are followed by fewer financial analysts than other stocks. The shunning leads to an outperformance of dirty stocks in cross-sectional and time-series return analyses. These observations affect all firms within a dirty industry, regardless of whether they have high or low TRI emissions. This means that comparatively clean firms are shunned by capital market participants simply because of their industry affiliation, which can result in financing disadvantages and low incentives to improve sustainability performance. Thus, our findings contribute to the understanding of environmental preferences of investors and their consequences for asset pricing.
Keywords: 330